Determinants of competitiveness and their relative importance: a study of Indian auto-component industry. (2nd November 2011) - Joshi, Deepika; Rathore, Ajay Pal Singh; Sharma, Dipti; Nepal, Bimal
A focused study on determinants of competitiveness for Indian automotive component industry in special context to supply chain activities is presented. The paper delineates the relative importance of various determinants of competitiveness by using analytic network process (ANP). A set of 24 determinants identified through a survey and face-to-face interviews is presented. The survey results find that customer demand to be the most important element for the competitiveness. It further unveils dependency among all the 24 metrics of competitiveness prompting the need for trade-offs amongst the factors. The proposed methodology and findings of the research can provide the supply chain managers and strategists with an important business intelligence and analytical tool to integrate their supply chain strategy with corporate strategy considering the impact of individual factors on overall industrial growth.